Evaluation of Postoperative Analgesia in Patients Undergoing Laparoscopic Cholecystectomy under General Anaesthesia: With or Without Bupivacaine Instillation in Gall Bladder Fossa - Pradhan, Suresh; Shrestha, Amir Babu (Nepal Journal of Medical Sciences, 2024)
Introduction: Laparoscopic Cholecystectomy is now the gold standard treatment of symptomatic gallstones. Post-surgery, patients suffer visceral and shoulder pain secondary to peritoneal insufflation. This study evaluates the analgesic effectiveness of 0.25% bupivacaine instillation in gall bladder fossa after laparoscopic cholecystectomy. Methods: A prospective, double-blind study was conducted in 60 patients aged 20-60 years, ASA I and II, weighing 40-80 kgs, undergoing laparoscopic cholecystectomy under general anaesthesia. Patients were divided into two groups: Group A (30 patients) received 10 ml of 0.25% Bupivacaine, and Group B (30 patients) received 10ml Normal Saline in gall bladder fossa post-surgery. Postoperative pain was accessed using the visual analogue scale at 6, 12 and 24 hours postoperatively. Data were applied with appropriate statistical tests, results with p value <0.05 were considered significant. Results: Demographic data were comparable in both groups (p>0.05). VAS score was significantly lower in group A(1.10± 0.76) compared to group B(2.73± 1.62)(p=0.00) at 6 hours postoperatively. VAS scores were comparable at 12 and 24 hours postoperatively. Rescue analgesic use was significantly less in group A (0%) compared to group B (20%) in the first 6 hours postoperatively (p=0.01). Rescue analgesia requirements were comparable and statistically insignificant for the rest of the study duration (p=0.79; p=0.64). Conclusions: Postoperative pain was lower in patients receiving bupivacaine instillation in gall bladder fossa compared to those receiving normal saline during first six postoperative hours. VAS scores and rescue analgesic requirements were comparable on rest of the study duration.